(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Mobile edge computing development (MEC). All Internet of Things devices at mobile edge use wireless networking. Therefore, protecting the sender’s data and privacy during transmission is of utmost importance. The current state of user authentication techniques in MEC is crowded with proposals from several researchers. Unfortunately, there is currently no lightweight and efficient method of authenticating between users, edge devices, and the cloud server. In this research, we develop a mechanism for secure authentication and key agreement between three parties that does not rely on bilinear pairings. The suggested protocol enabled authentication between end users, edge devices, and the cloud server, and it also enabled the three parties to perform key agreement in order to establish a shared session key. Our protocol is safe and secure according to the security analysis, since it satisfies security criteria including session-key security and forward secrecy. A little amount of computing is required for this technique, as shown experimentally.